Financing model for demand response information services with bundled incentives - Yuliza, Evi; Puspita, Fitri Maya; Rahayu, Fridha Aprisa (Institute of Advanced Engineering and Science, 2025)
This study attempts to build a new model for information service financing schemes by considering utility functions to measure heterogeneous consumer satisfaction. This model was developed by involving a combination of reverse charging, demand response, and heterogeneous incentive models, and considering the quality of user service measured by a quasi-linear utility function against the information service financing scheme. The incentive financing scheme is applied to a local data server, including traffic during peak hours and off-peak hours. This internet incentive financing model is solved using the LINGO 13.0 application. Furthermore, the development model for incentive financing for information services based on demand response and bundling in the information service financing scheme is subjected to sensitivity analysis with the aim of identifying parameters that affect model performance. Based on the analysis that has been done, the results of this study indicate that the new model in the incentive financing scheme for information services with a quasi-linear utility function involving a combination of reverse charging, demand response, and heterogeneous incentive models produces an optimal solution in a fixed cost financing scheme for data traffic usage during peak hours and off-peak hours.